# SOLUTION: solve the system using the substitution method. 2x+y=6 3x+5y=9

Algebra ->  Algebra  -> College  -> Linear Algebra -> SOLUTION: solve the system using the substitution method. 2x+y=6 3x+5y=9      Log On

 Algebra: Linear Algebra (NOT Linear Equations) Solvers Lessons Answers archive Quiz In Depth

Question 218668: solve the system using the substitution method.
2x+y=6
3x+5y=9

Found 2 solutions by drj, MathTherapy:
Answer by drj(1380)   (Show Source):
You can put this solution on YOUR website!
solve the system using the substitution method.
2x+y=6
3x+5y=9

Solved by pluggable solver: SOLVE linear system by SUBSTITUTION
Solve:
We'll use substitution. After moving 1*y to the right, we get:
, or . Substitute that
into another equation:
and simplify: Error: 'Can't call method "invoke_solver" on an undefined value at /home/ichudov/project_locations/algebra.com/templates/Algebra/Solver/PerlSolver.pm line 115. Can't call method "invoke_solver" on an undefined value at /home/ichudov/project_locations/algebra.com/templates/Algebra/Solver/PerlSolver.pm line 115. '. Can't call method "invoke_solver" on an undefined value at /home/ichudov/project_locations/algebra.com/templates/Algebra/Solver/PerlSolver.pm line 115. Can't call method "invoke_solver" on an undefined value at /home/ichudov/project_locations/algebra.com/templates/Algebra/Solver/PerlSolver.pm line 115.
error_location: 101

I hope the above steps were helpful.

For FREE Step-By-Step videos in Introduction to Algebra, please visit http://www.FreedomUniversity.TV/courses/IntroAlgebra and for Trigonometry visit http://www.FreedomUniversity.TV/courses/Trigonometry.

Good luck in your studies!

Respectfully,
Dr J
Answer by MathTherapy(1483)   (Show Source):
You can put this solution on YOUR website!
solve the system using the substitution method.
2x+y=6
3x+5y=9

As it's easiest to solve for y in eq (i), we do just that to get: y = - 2x + 6

We now substitute this value, - 2x + 6 for y in eq (ii) to get: 3x + 5(- 2x + 6) = 9

3x - 10x + 30 = 9

- 7x = - 21

=

Substitute 3 for x in eq (i), 3x + 5y = 9 to get: 3(3) + 5y = 9

9 + 5y = 9

5y = 0

=